MENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN METODE EXCAMPLE NON EXCAMPLE PADA SISWA KELAS IV SD NEGERI 004 KEPENUHAN - sugianto sugianto (STKIP ROKANIA, 2018)
This study aims to improve the results of mathematics learning by using excample non example in fourth grade students of SD Negeri 004 Kepenuhan Rokan Hulu. The subjects of this study are students of class IV which amounted to 20 students. Classroom action research is conducted in 2 cycles. Data collection in this study using the results of tests and observations. The results showed that learning by using the media images can improve the results of learning mathematics class IV SD 004 Kepenuhan. In the initial condition of the result before the action is given an average value of 65.20. In cycle I using example non excample class average value increased to 77.50. In cycle II showed an increase with the average obtained 90.70